Sludge conditioner with nanoscale hydrophobic material loaded with multi-core metal chelate and preparation method of sludge conditioner
Through the combination of nano-scale hydrophobic materials loaded with multi-core metal chelates and degradable polymerizable organic alkali, the problem of poor dehydration performance of existing sludge dehydration agents is solved, efficient sludge dehydration and cost reduction are achieved, and sludge reduction is met Quantitative and harmless demand.
Patent Information
- Application Number
- CN202411549031.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing sludge dehydrating agents have poor dehydration performance, large amount of agent addition, large sludge increase and high cost in sludge treatment, making it difficult to effectively solve the problems of sludge reduction and harmlessness.
Using nano-scale hydrophobic materials to load multi-core metal chelates, the sludge conditioner is used in a coordinated manner through the combination of hydrophobic materials, coordination iron chelators and multi-core metal catalysts, to destroy the EPS of the sludge system and release the combination Water reduces electrostatic repulsion and improves the hydrophobicity of the sludge, thereby achieving efficient dehydration.
It significantly improves the dehydration performance of sludge, reduces the incremental sludge and desludge costs, extends the service life of the equipment, realizes rapid and continuous dehydration of sludge and solid-liquid separation, and achieves the real purpose of reducing volume and body.
Smart Images

Figure CN119263588A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sludge conditioning and dehydration, and in particular relates to a sludge conditioner of a nano-scale hydrophobic material loaded with a multi-nuclear metal chelate and a preparation method thereof. Background Art
[0002] Nowadays, the treatment and disposal of domestic sludge has become a prominent environmental problem that the whole society urgently needs to face and solve, especially the reduction and harmlessness of sludge. In recent years, under the guidance of policy planning standards issued by the state and local governments, the scale of the domestic sludge dewatering industry has also expanded rapidly. According to data, the market size of my country's sludge dewatering industry in 2022 is about 14.109 billion yuan, a year-on-year increase of 7.25%. From the perspective of market segments, in 2022, the mechanical dewatering market accounted for about 24.1% of my country's sludge dewatering industry market, and the energy drying and other markets accounted for 75.9%.
[0003] In the domestic market of sludge dewatering agents, with the gradual improvement of domestic urban sewage treatment infrastructure construction, the urban sewage treatment industry has developed rapidly, and water environment governance has also achieved remarkable results. From the perspective of the sludge dewatering agent market size, since 2012, the market size of my country's sludge dewatering agent industry has increased year by year. According to statistics, the market size of my country's sludge dewatering agent industry in 2022 is about 2.08 billion yuan, a year-on-year increase of 7.3%. In terms of market segments, organic sludge dewatering agents occupy the mainstream position in the market, accounting for about 55.6% of the market in 2022, followed by inorganic sludge dewatering agents, accounting for 25.1% of the market.
[0004] Sludge dewatering pretreatment is an indispensable part of sewage / sludge treatment. At present, the sludge dewatering agents on the market generally use a combination of "iron, aluminum salt + organic flocculant PAM or lime", but they generally have disadvantages such as poor dewatering performance, large dosage of agents, large sludge increment, and high cost. Therefore, there is an urgent need for an efficient, green and environmentally friendly desludge agent to solve the industry's pain points. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a sludge conditioner of a nano-scale hydrophobic material loaded with a multi-core metal chelate and a preparation method thereof. The present invention applies the technical solution of a combination of two products of a hydrophobic material loaded with a coordinated iron chelating agent and a multi-core metal catalyst in combination with a degradable polymeric organic base to a sludge dewatering process, thereby destroying the EPS of the sludge system, dissolving microbial cells in the sludge, releasing bound water in the sludge, reducing electrostatic repulsion, improving the hydrophobicity of microbial cells in the sludge, releasing free water and surface water, and greatly improving the dewatering performance of the sludge. The corrosion rate of pipelines and equipment is effectively slowed down, and the sludge increment is greatly reduced.
[0006] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.
[0007] The first aspect of the present invention provides a sludge conditioner of a nano-scale hydrophobic material loaded with a multi-core metal chelate. The sludge conditioner comprises the following components in weight percentage: 10-20% of a hydrophobic material, 30-35% of a chelated iron solution, 10-15% of a multi-core metal salt, 5%-10% of a dispersant, 2-5% of a pH adjuster, and the remainder of deionized water.
[0008] In a preferred embodiment of the present invention, the hydrophobic material is selected from bentonite, attapulgite, diatomaceous earth, montmorillonite, zeolite powder, or a mixture of two or more thereof.
[0009] In a preferred embodiment of the present invention, the chelated iron solution is a mixed solution of a chelating agent and an iron salt in a molar ratio of 2:1-5:1.
[0010] In a preferred embodiment of the present invention, the chelating agent is selected from any one of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, ethylenediamine disuccinic acid, citric acid, or a mixture of two or more thereof.
[0011] In a preferred embodiment of the present invention, the iron salt is ferric sulfate and / or ferrous sulfate; when the iron salt is ferric sulfate and ferrous sulfate, the molar ratio of ferric sulfate to ferrous sulfate is 5:5 to 7:3.
[0012] In a preferred embodiment of the present invention, the polynuclear metal salt is selected from one of aluminum sulfate, aluminum chloride, magnesium sulfate, aluminum silicate, and zinc sulfate, or a mixture of two or more thereof.
[0013] In a preferred embodiment of the present invention, the dispersant is selected from one or a mixture of two or more of sodium polyacrylate, polyvinyl pyrrolidone, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, and polyvinyl alcohol.
[0014] In a preferred embodiment of the present invention, the pH adjuster is sodium hydroxide and / or potassium hydroxide.
[0015] The second aspect of the present invention provides a method for preparing a sludge conditioner comprising a nano-scale hydrophobic material loaded with a multi-core metal chelate, the method comprising the following steps:
[0016] S1: dissolving the nano-hydrophobic material in deionized water and mixing and stirring evenly;
[0017] S2: Add dispersant to S1 according to weight ratio under stirring;
[0018] S3: while S2 is in a stirring state, adding the chelated iron solution and the polynuclear metal salt to S2 in sequence to obtain a mixed solution;
[0019] S4: The mixed solution obtained in S3 is placed in a microwave and heated at 40-60°C for 30 minutes. After the reaction is completed, a pH adjuster is added, and the mixture is mixed and stirred evenly to obtain the product.
[0020] In a preferred embodiment of the present invention, the preparation method of the chelated iron solution is:
[0021] S1: weighing and mixing ferric sulfate and ferrous sulfate in a molar ratio of 5:5 to 7:3 to obtain an iron salt;
[0022] S2: Add iron salt to deionized water, keep stirring, add chelating agent, continue to stir evenly, adjust the pH of the solution between 8.0 and 10.0, and continue stirring for 0.5h to obtain a chelated iron solution.
[0023] The third aspect of the present invention provides a degradable polymeric organic base for sludge wall breaking and dehydration. The polymeric organic base comprises the following components in weight percentage: 5-10% cationic surfactant, 10-20% polymeric organic base, 2-5% persulfate, 1-3% pH regulator, and the remainder deionized water.
[0024] In a preferred embodiment of the present invention, the cationic surfactant is selected from one or a mixture of two or more of dodecyldimethylbenzylammonium chloride, tetradecyldimethylbenzylammonium chloride, dodecyltrimethylammonium chloride and hexadecyltrimethylammonium chloride.
[0025] In a preferred embodiment of the present invention, the polymeric organic base is polydimethyldiallylammonium chloride and / or polyamine.
[0026] In a preferred embodiment of the present invention, the persulfate is selected from one or a mixture of two or more of potassium persulfate, sodium persulfate, and ammonium persulfate.
[0027] In a preferred embodiment of the present invention, the pH adjuster is sodium hydroxide and / or potassium hydroxide.
[0028] A fourth aspect of the present invention provides a method for preparing a degradable polymeric organic base for sludge wall breaking and dehydration, the method comprising the following steps:
[0029] S1: Evenly stir the pH regulator and deionized water in a weight ratio of 1:20-60 to prepare a mixed solution A;
[0030] S2: uniformly stirring the persulfate and the mixed solution A according to weight parts to prepare a mixed solution B;
[0031] S3: Add cationic surfactant and polymeric organic base to the mixed solution B in parts by weight, stir evenly, and prepare a liquid wall-breaking agent.
[0032] The fifth aspect of the present invention provides a composite sludge conditioner, comprising the aforementioned sludge conditioner of the nano-scale hydrophobic material loaded with multi-core metal chelate, and the aforementioned degradable polymeric organic base for sludge wall breaking and dehydration.
[0033] In a preferred embodiment of the present invention, the mass ratio of the sludge conditioner of the nano-scale hydrophobic material loaded with multi-core metal chelate to the degradable polymeric organic base for sludge wall breaking and dehydration is (600-1000): (85-120).
[0034] By means of the above technical solution, the present invention has at least the following advantages:
[0035] 1. In one aspect of the present invention, the nano-scale chelating suspension component produced by using hydrophobic materials to load coordinated iron chelating agents in conjunction with multi-nuclear metal catalysts and other raw materials greatly enhances the product's double electrical layer, electrical neutralization, and net-catching effects, and improves the bridging, flocculation, and rapid sedimentation effects.
[0036] 2. In another aspect of the present invention, a high-density positively charged cloud is formed by the chain breaking, decomposition, and ionization of the degradable polymeric organic base component, thereby achieving the destabilization of the negatively charged colloidal particles, so that the water in the colloidal organic matter is completely broken through the wall and the gel to release the intracellular water and interstitial water, and the dispersed organic colloids form micro-flocs with different positively charged clouds; the destabilization, wall breaking, and gel breaking are utilized to increase the release of interstitial water content and reduce seepage resistance; the sludge colloidal system is destroyed and then flocculated, thereby achieving the maximum separation of mud and water and reducing the sludge water content.
[0037] 3. In the actual application process, the composite sludge conditioner of the present invention can not only achieve a moisture content of less than 60% in the treated mud cake, but also reduce the desludging cost by 20-40%. The composite sludge conditioner of the invention has excellent dehydration effect on sludge produced by municipal sewage, industrial park sewage and enterprise sewage in plate and frame filter press, centrifuge, screw stacking and other treatment processes. The main advantages are as follows: 1) The hydrophobic material-loaded coordinated iron chelating agent cooperates with the multi-core metal catalyst composite product, which has the functions of coordination, chelation, catalysis, bridging, flocculation, double electric layer neutralization, net capture, etc., and quickly settles to achieve rapid and continuous dehydration of sludge, achieve solid-liquid separation, control the moisture content of the mud cake to less than 60%, achieve the purpose of real reduction in volume and volume, and save disposal costs; 2) Replace inorganic salt flocculants / coagulants and lime products to greatly reduce sludge increment; 3) Reduce filter cloth clogging and extend service life; 4) Help increase the proportion of organic matter in sludge, which is beneficial to subsequent composting and other rural greening projects.
[0038] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The figure is a process flow chart of sludge dehydration using the conditioner of the present invention. DETAILED DESCRIPTION
[0040] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The present invention obtains a composite sludge conditioner by combining a hydrophobic material loaded coordinated iron chelating agent with a multi-nuclear metal catalyst and a degradable polymeric organic base. First, the multivalent iron atoms and iron ions in the coordinated iron chelating agent component and the organic ligands with lone pairs of electrons form cyclic monomer molecules with strong complexing ability. These monomer molecules are synergistically compounded with a multi-nuclear metal catalyst containing potassium, aluminum, iron, and magnesium, and are connected to each other by van der Waals forces, electric dipole moment polarization forces, and hydrogen bonds to form long-chain helical chelates, thereby having the effects of coordination, chelation, catalysis, penetration, bridging, flocculation, double-layer neutralization, net capture and sweeping; secondly, the combined degradable polymeric organic base product is a product containing superoxide anions (O2 - ), hydroxyl radical (OH - ) and a-oxygen and other active oxygen groups linear polymerized organic base mixture, sludge microorganisms contain 30-60% protein, and the active oxygen groups have a targeted function to destroy the protein, and this destructive reaction is the process of organic base chain breaking, decomposition into small molecules and destruction of the extracellular polymers of the sludge system; finally, the composite sludge conditioner of the present invention can destroy the EPS of the sludge system, dissolve the microbial cells in the sludge, release the bound water and interstitial water in the sludge, reduce the electrostatic repulsion, improve the hydrophobicity of the microbial cells in the sludge, release the free water and surface water, and greatly improve the dewatering performance of the sludge.
[0042] The composite sludge conditioner is obtained by combining "nano-scale hydrophobic material loaded multi-core metal chelate sludge conditioner (agent A) + degradable polymeric organic base for sludge wall breaking and dehydration (agent B)". The innovation lies in the development of a new type of sludge dehydration agent combination product to replace lime, iron salt and aluminum salt. Among them, agent A is a homogeneous mixed suspension after the reaction of nano-scale silicon-based hydrophobic material loaded coordinated iron chelate and multi-core metal catalyst; agent B is a degradable polymeric organic base product containing active oxygen groups generated by unsaturated organic base under oxygen-rich conditions. The combination of agent A and agent B can fully break the cell wall of organic biomass in the sludge, destroy the EPS of the sludge system, dissolve microbial cells in the sludge, release bound water and interstitial water in the sludge, and reduce electrostatic repulsion. The addition of hydrophobic materials provides a skeleton channel for sludge dehydration, improves the hydrophobicity of microbial cells in the sludge, releases free water and surface water, and makes water permeation smooth without clogging the filter material, reducing equipment loss and maintenance, and greatly improving work efficiency.
[0043] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0044] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0045] Embodiment 1:
[0046] Preparation of chelated iron solution: weigh each raw material of ferric sulfate and ferrous sulfate in a molar ratio of 5:5, mix and obtain iron salt; add the iron salt to deionized water, keep stirring, add ethylenediaminetetraacetic acid (add with the iron salt in a molar ratio of 3.5:1), continue to stir evenly, adjust the pH of the solution to 9.0, continue stirring for 0.5h, and obtain the chelated iron solution.
[0047] Preparation of sludge conditioner:
[0048] The following raw materials were prepared according to weight percentage: 15% bentonite, 32.5% chelated iron solution, 12.5% aluminum sulfate, 7.5% sodium polyacrylate, 3.5% sodium hydroxide and the balance deionized water.
[0049] S1: dissolving bentonite in deionized water and mixing and stirring uniformly; S2: adding sodium polyacrylate to S1 according to weight ratio under stirring conditions; S3: while S2 is in a stirring state, adding chelated iron solution and aluminum sulfate to S2 in sequence to obtain a mixed solution; S4: heating the obtained mixed solution in S3 under microwave at 50°C for 30 minutes, and after the reaction is completed, adding sodium hydroxide, mixing and stirring uniformly to obtain the obtained solution.
[0050] Embodiment 2:
[0051] Preparation of chelated iron solution: weigh each raw material of ferric sulfate and ferrous sulfate in a molar ratio of 6:4, mix and obtain iron salt; add the iron salt to deionized water, keep stirring, add disodium ethylenediaminetetraacetic acid (add with the iron salt in a molar ratio of 2:1), continue to stir evenly, adjust the pH of the solution to 10.0, continue to stir for 0.5h, and obtain the chelated iron solution.
[0052] Preparation of sludge conditioner:
[0053] The following raw materials are prepared according to weight percentage: 20% attapulgite, 30% chelated iron solution, 10% aluminum chloride, 10% polyvinyl pyrrolidone, 2% sodium hydroxide and the balance deionized water.
[0054] S1: dissolving attapulgite in deionized water and mixing and stirring evenly; S2: adding polyvinyl pyrrolidone to S1 according to weight ratio under stirring condition; S3: while S2 is in a stirring state, adding chelated iron solution and aluminum chloride to S2 in sequence to obtain a mixed solution; S4: heating the mixed solution obtained in S3 under microwave at 50°C for 30 minutes, adding sodium hydroxide after the reaction is completed, mixing and stirring evenly to obtain the product.
[0055] Embodiment 3:
[0056] Preparation of chelated iron solution: weigh each raw material of ferric sulfate and ferrous sulfate in a molar ratio of 7:3, mix and obtain iron salt; add the iron salt to deionized water, keep stirring, add ethylenediamine disuccinic acid (add with the iron salt in a molar ratio of 5:1), continue to stir evenly, adjust the pH of the solution to 8.0, continue stirring for 0.5h, and obtain the chelated iron solution.
[0057] Preparation of sludge conditioner:
[0058] The following raw materials were prepared according to weight percentage: 10% diatomaceous earth, 35% chelated iron solution, 15% aluminum silicate, 5% sodium dodecyl sulfate, 5% sodium hydroxide and the balance deionized water.
[0059] S1: dissolving diatomaceous earth in deionized water and mixing and stirring uniformly; S2: adding sodium dodecyl sulfate to S1 according to weight ratio under stirring conditions; S3: while S2 is in a stirring state, adding chelated iron solution and aluminum silicate to S2 in sequence to obtain a mixed solution; S4: heating the mixed solution obtained in S3 under microwave at 50°C for 30 minutes, and after the reaction is completed, adding sodium hydroxide, mixing and stirring uniformly to obtain the product.
[0060] Comparative Example 1:
[0061] The same as Example 1, the only difference is that the sludge conditioner does not contain bentonite.
[0062] Comparative Example 2:
[0063] The same as Example 1, the only difference is that the sludge conditioner does not contain chelated iron solution.
[0064] Comparative Example 3:
[0065] The same as Example 1, the only difference is that the sludge conditioner does not contain bentonite and chelated iron solution.
[0066] Embodiment 4:
[0067] The following raw materials were prepared according to weight percentage: 7.5% dodecyldimethylbenzyl ammonium chloride, 15% polydimethyldiallyl ammonium chloride, 3.5% potassium persulfate, 2% sodium hydroxide, and the balance deionized water.
[0068] S1: Sodium hydroxide and deionized water are uniformly stirred in a weight ratio of 1:40 to prepare a mixed solution A; S2: Potassium persulfate and the mixed solution A are uniformly stirred in parts by weight to prepare a mixed solution B; S3: Dodecyl dimethyl benzyl ammonium chloride and poly dimethyl diallyl ammonium chloride are added to the mixed solution B in parts by weight in sequence, and stirred uniformly to prepare a liquid wall-breaking agent.
[0069] Embodiment 5:
[0070] The following raw materials are prepared according to weight percentage: 10% tetradecyldimethylbenzyl ammonium chloride, 10% polydimethyldiallyl ammonium chloride, 5% sodium persulfate, 1% sodium hydroxide, and the balance deionized water.
[0071] S1: Sodium hydroxide and deionized water are uniformly stirred in a weight ratio of 1:40 to prepare a mixed solution A; S2: Sodium persulfate and the mixed solution A are uniformly stirred in parts by weight to prepare a mixed solution B; S3: Tetradecyl dimethyl benzyl ammonium chloride and polydimethyl diallyl ammonium chloride are added to the mixed solution B in parts by weight in sequence, and stirred uniformly to prepare a liquid wall-breaking agent.
[0072] Embodiment 6:
[0073] The following raw materials are prepared according to weight percentage: 5% dodecyltrimethylammonium chloride, 20% polydimethyldiallylammonium chloride, 2% ammonium persulfate, 3% sodium hydroxide, and the balance deionized water.
[0074] S1: Sodium hydroxide and deionized water are uniformly stirred in a weight ratio of 1:40 to prepare a mixed solution A; S2: Ammonium persulfate and the mixed solution A are uniformly stirred in parts by weight to prepare a mixed solution B; S3: Dodecyltrimethylammonium chloride and polydimethyldiallylammonium chloride are sequentially added to the mixed solution B in parts by weight, and stirred uniformly to prepare a liquid wall-breaking agent
[0075] Comparative Example 4:
[0076] The same as Example 4, the only difference is that the degradable polymeric organic base does not contain dodecyl dimethyl benzyl ammonium chloride.
[0077] Comparative Example 5:
[0078] The same as Example 4, the only difference is that the degradable polymeric organic base does not contain polydimethyldiallylammonium chloride.
[0079] Comparative Example 6:
[0080] The same as Example 4, the only difference is that the degradable polymeric organic base does not contain dodecyldimethylbenzyl ammonium chloride and polydimethyldiallylammonium chloride.
[0081] Embodiment 7:
[0082] The sludge conditioner prepared in Example 1 and the degradable polymeric organic base prepared in Example 4 were mixed in a mass ratio of 1000:120 to obtain a composite sludge conditioner.
[0083] Embodiment 8:
[0084] The sludge conditioner prepared in Example 1 and the degradable polymeric organic base prepared in Example 4 were mixed in a mass ratio of 800:100 to obtain a composite sludge conditioner.
[0085] Embodiment 9:
[0086] The sludge conditioner prepared in Example 1 and the degradable polymeric organic base prepared in Example 4 were mixed in a mass ratio of 660:90 to obtain a composite sludge conditioner.
[0087] Embodiment 10:
[0088] The sludge conditioner prepared in Example 1 and the degradable polymeric organic base prepared in Example 4 were mixed in a mass ratio of 600:85 to obtain a composite sludge conditioner.
[0089] Test Example 1: Testing the effect of different sludge conditioners on sludge dewatering in a municipal sewage treatment plant in Beijing
[0090] 1. Sludge dewatering treatment process flow chart Figure 1 .
[0091] in,
[0092] 1) Conditioning tank volume m 3 (100*2); conditioning time min (30min);
[0093] 2) Inlet mud moisture content % (about 98%); Dewatered mud cake moisture content % (≤ 60%);
[0094] 3) Sludge moisture content implementation standard: GB24188-2009, 60% moisture content;
[0095] 4) Plate and frame equipment type: Jingjin plate and frame filter press (2 units), plate and frame filtration area 450m 2 .
[0096] 2. Sludge dewatering process operation and equipment control parameters
[0097] 1) Mud inflow volume m 3 / batch (50~80); Mud production per plate frame t / batch (1.5~1.8t absolute dry);
[0098] 2) Low-pressure feed pressure MPa (0.6); low-pressure feed time s (2000);
[0099] 3) High-pressure feed pressure MPa (1.1); High-pressure feed time s (2500);
[0100] 4) Pressing pressure MPa (1.6); constant pressure pressing time s (3600);
[0101] 5) Operating time / batch (about 4 hours); number of operating batches / day (2 to 7).
[0102] The above-mentioned process and parameters were used to carry out sludge dehydration treatment on the products obtained in Examples 1-10 and Comparative Examples 1-6. The results are shown in Table 1.
[0103] Table 1 Detection of the effect of different sludge conditioners on sludge dewatering
[0104]
[0105]
[0106] Note: The amount of sludge input is a measure of the speed of sludge filtration, and is also an indirect measure of the softness and hardness of the mud cake. Because the filter chamber space of the plate and frame filter press is fixed, a large amount of sludge input indicates that the sludge has good hydrophobicity and water filtration properties, and is easy to squeeze. The more sludge input, the higher the sludge expansion per unit volume. The larger the sludge volume, the more conducive it is to squeezing, and the drier the squeezed mud cake.
[0107] In the table: A refers to the sludge conditioner composed of nano-scale hydrophobic material loaded with multi-core metal chelate; B refers to the degradable polymeric organic base used for sludge wall breaking and dehydration.
[0108] From the results in Table 1, we can see that:
[0109] (1) Both the hydrophobic material and the chelated iron solution play a certain synergistic role in the sludge dehydration of the sludge conditioner (agent A) loaded with nano-scale hydrophobic material and multi-core metal chelate;
[0110] (2) Cationic surfactants and polymeric organic bases both play a certain synergistic role in the degradable polymeric organic base (agent B) used for sludge wall breaking and dehydration;
[0111] (3) The sludge conditioner (agent A) loaded with a nano-scale hydrophobic material and a multi-core metal chelate and a degradable polymeric organic base (agent B) for sludge wall breaking and dehydration are used together. The sludge dehydration effect is better than that of a single use, achieving the technical effect of the product combination "1+1>2";
[0112] (4) The combination of a sludge conditioner (agent A) loaded with a nano-scale hydrophobic material and a colloidal tissue disruptor (agent B) increases the proportion of the degradable polymeric organic base (agent B) used for sludge wall breaking and dehydration, which helps to increase the efficiency of the product.
[0113] Test Example 2: Detection of the effect of different sludge conditioners on the dehydration of high organic matter sludge from a sewage treatment plant in Gansu
[0114] 1. Sludge dewatering treatment process flow chart Figure 1 .
[0115] 1) Conditioning tank volume m 3 (175.5*4); conditioning time min (90min);
[0116] 2) Inlet mud moisture content % (98%~96%); Dewatered mud cake moisture content % (≤60%);
[0117] 3) Sludge moisture content implementation standard: GB24188-2009, 60% moisture content;
[0118] 4) Plate and frame equipment type: Jingjin plate and frame filter press (8 units), plate and frame filtration area 800m 2 .
[0119] 2. Sludge dewatering process control parameters
[0120] 1) Mud inflow volume m 3 / batch (about 100); mud production per plate frame t / batch (2.5-3.5t absolute dry);
[0121] 2) Low-pressure feed pressure MPa (0.8); low-pressure feed time s (9000);
[0122] 3) High-pressure feed pressure MPa (1.2); High-pressure feed time s (3600);
[0123] 4) Pressing pressure MPa (1.4); constant pressure pressing time s (2700);
[0124] 5) Running time per plate / batch (about 270 minutes); number of running batches / day (28).
[0125] The above process and parameters were used to carry out sludge dewatering treatment on the products obtained in Examples 1, 4, 7 and Comparative Examples 1-6. The results are shown in Table 2.
[0126] Table 2 Detection of the effect of different sludge conditioners on sludge dewatering
[0127]
[0128] From the results in Table 2, we can see that:
[0129] (1) Both the hydrophobic material and the chelated iron solution have a certain synergistic effect on the sludge dehydration of the sludge conditioner (agent A) loaded with nano-scale hydrophobic materials and multi-core metal chelates;
[0130] (2) Cationic surfactants and polymeric organic bases both play a certain synergistic role in the degradable polymeric organic base (agent B) used for sludge wall breaking and dehydration;
[0131] (3) The sludge conditioner (agent A) loaded with a nano-scale hydrophobic material and a multi-core metal chelate and a degradable polymeric organic base (agent B) for sludge wall breaking and dehydration are used together. The sludge dehydration effect is better than that of a single use, achieving the technical effect of the product combination "1+1>2";
[0132] (4) For high-organic matter sludge, the sludge conditioner (agent A) composed of nano-hydrophobic materials loaded with multi-core metal chelates and the degradable polymeric organic base (agent B) used for sludge wall breaking and dehydration have the advantages of low dosage and good sludge dehydration effect, and avoid the introduction of large amounts of lime, with low sludge increment. While reducing the cost of sludge disposal, it also effectively reduces the transportation cost of sludge.
[0133] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A sludge conditioner comprising a nano-scale hydrophobic material loaded with a multi-nuclear metal chelate, characterized in that: The sludge conditioner comprises the following components in percentage by weight: 10-20% of hydrophobic material, 30-35% of chelated iron solution, 10-15% of polynuclear metal salt, 5%-10% of dispersant, 2-5% of pH adjuster, and the balance of deionized water.
2. The sludge conditioner of the nano-scale hydrophobic material loaded multi-nuclear metal chelate according to claim 1, characterized in that: The hydrophobic material is selected from bentonite, attapulgite, diatomaceous earth, montmorillonite, zeolite powder, or a mixture of two or more thereof.
3. The sludge conditioner of the nano-scale hydrophobic material loaded multi-nuclear metal chelate according to claim 1, characterized in that: The chelated iron solution is a mixed solution formed by mixing a chelating agent and an iron salt in a molar ratio of 2:1-5:
1.
4. The sludge conditioner of the nano-scale hydrophobic material loaded multi-nuclear metal chelate according to claim 3, characterized in that: The chelating agent is selected from any one of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, ethylenediamine disuccinic acid, and citric acid, or a mixture of two or more thereof.
5. The sludge conditioner of the nano-scale hydrophobic material loaded multi-nuclear metal chelate according to claim 3, characterized in that: The iron salt is ferric sulfate and / or ferrous sulfate; when the iron salt is ferric sulfate and ferrous sulfate, the molar ratio of the ferric sulfate to the ferrous sulfate is 5:5 to 7:
3.
6. The sludge conditioner of the nano-scale hydrophobic material loaded multi-nuclear metal chelate according to claim 1, characterized in that: The polynuclear metal salt is selected from one of aluminum sulfate, aluminum chloride, magnesium sulfate, aluminum silicate, and zinc sulfate, or a mixture of two or more thereof; The dispersant is selected from one or a mixture of two or more of sodium polyacrylate, polyvinyl pyrrolidone, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, and polyvinyl alcohol; The pH adjuster is sodium hydroxide and / or potassium hydroxide.
7. A method for preparing a sludge conditioner comprising a nano-scale hydrophobic material loaded with a multi-nuclear metal chelate according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: S1: dissolving the nano-hydrophobic material in deionized water and mixing and stirring evenly; S2: Add dispersant to S1 according to weight ratio under stirring; S3: while S2 is in a stirring state, adding the chelated iron solution and the polynuclear metal salt to S2 in sequence to obtain a mixed solution; S4: The mixed solution obtained in S3 is placed in a microwave and heated at 40-60°C for 30 minutes. After the reaction is completed, a pH adjuster is added, and the mixture is mixed and stirred evenly to obtain the product.
8. The preparation method according to claim 7, characterized in that: The preparation method of the chelated iron solution is: S1: weighing and mixing ferric sulfate and ferrous sulfate in a molar ratio of 5:5 to 7:3 to obtain an iron salt; S2: Add iron salt to deionized water, keep stirring, add chelating agent, continue to stir evenly, adjust the pH of the solution between 8.0 and 10.0, and continue stirring for 0.5h to obtain a chelated iron solution.
9. A degradable polymeric organic base for sludge wall breaking and dehydration, characterized in that: The polymeric organic base comprises the following components in weight percentage: 5-10% of a cationic surfactant, 10-20% of a polymeric organic base, 2-5% of a persulfate, 1-3% of a pH regulator, and the balance of deionized water.
10. The degradable polymeric organic base for sludge wall breaking and dehydration according to claim 9, characterized in that: The cationic surfactant is selected from one or a mixture of two or more of dodecyl dimethyl benzyl ammonium chloride, tetradecyl dimethyl benzyl ammonium chloride, dodecyl trimethyl ammonium chloride, and hexadecyl trimethyl ammonium chloride; The polymeric organic base is polydimethyldiallylammonium chloride and / or polyamine; The persulfate is selected from one or a mixture of two or more of potassium persulfate, sodium persulfate, and ammonium persulfate; The pH regulator is sodium hydroxide and / or potassium hydroxide.
11. A method for preparing a degradable polymeric organic base for sludge wall breaking and dehydration according to claim 9 or 10, characterized in that: The method comprises the following steps: S1: Evenly stir the pH regulator and deionized water in a weight ratio of 1:20-60 to prepare a mixed solution A; S2: uniformly stirring the persulfate and the mixed solution A according to weight parts to prepare a mixed solution B; S3: Add cationic surfactant and polymeric organic base to the mixed solution B in parts by weight, stir evenly, and prepare a liquid wall-breaking agent.
12. A composite sludge conditioner, characterized in that: A sludge conditioner comprising a nano-scale hydrophobic material loaded with a multi-core metal chelate as described in any one of claims 1 to 6, and a degradable polymeric organic base for sludge wall breaking and dehydration as described in claim 9 or 10.
13. The composite sludge conditioner according to claim 12, characterized in that: The mass ratio of the sludge conditioner of the nano-scale hydrophobic material loaded with multi-core metal chelate to the degradable polymeric organic base used for sludge wall breaking and dehydration is (600-1000): (85-120).
Citation Information
Patent Citations
Neutral inorganic composite material for dehydration, solidification and modification of high water content sludge
CN101955345A
Compound sludge dehydrating agent as well as preparation method and application thereof
CN106830621A
Sludge solidifying agent and preparation method and application thereof
CN109179935A
Combined conditioning agent for sludge deep dewatering and mud cake stabilization and application of combined conditioning agent
CN110217956A
Method for treating organic-wastes
KR1020100012798A
Cited By
Sludge dewatering conditioner, preparation method thereof and sludge dewatering process
CN120864776A